Therapeutic plasma exchange in pediatric patients of Guillain-Barre syndrome: Experience from a Tertiary Care Centre - Maitrey Gajjar; Tarak Patel; Nidhi Bhatnagar; Meghana Solanki; Vaidehi Patel; Shital Soni (Asian Journal of Transfusion Science, 2016)
Background and Objective: Therapeutic Plasma Exchange (TPE) is performed effectively and safely in adult patients, but the use of TPE is limited in paediatric patients due to lack of universally accepted indications and technical challenges like establishment of adequate vascular access, low blood volume, increased incidence of adverse events during procedure and poor co-operation of patients during procedure. We present our experience of TPE in paediatric patients to assess the effectiveness and safety of TPE in paediatric patients. Materials and Methods: A total 122 TPE procedures were performed in 40 paediatric patients between 3 to 15 years of age group with Guillain Barre Syndrome (GBS). TPE procedures were performed on alternate days depending on the clinical condition of the patient. Patient′s total blood volume was calculated as per Nadler′s formula and processed through central double lumen catheter. 1-1.5 plasma volume was exchanged with normal saline and fresh frozen plasma. Results: A total of 122 TPE procedures (with an average of three procedures per patient) were performed on 40 paediatric patients. More than three TPE procedures were performed in 29 patients, of which 27 patients showed improvement from grade-0 and grade-I to grade-III. One did not show any response and succumbed to the disease. Complications were observed in 14 patients which were well managed. Inadequate vascular access was most common complication observed in 11 patients. Conclusion: TPE in paediatric patients has been increasing and has been shown to be effective as first line or adjunctive therapy in selected diseases. It is safe procedure when volume shifts, calcium supplementation and venous access are taken care.